CONTRASTING ORIGINS OF EARLY CRETACEOUS BLACK SHALES IN THE VOCONTIAN BASIN: EVIDENCE FROM PALYNOLOGICAL AND CALCAREOUS NANNOFOSSIL RECORDS - Heimhofer U.; Herrle J.O.; Weissert H.; Hochuli P.A. (My University, 2006)
Detailed records of spore-pollen assemblages, particulate organic matter (OM), dinoflagellate cysts and calcareous nannofossils provide new insights into the palaeoclimatic and palaeoceanographic conditions during formation of Early Cretaceous black shales in the Vocontian basin (southeastern France). The early Aptian Niveau Goguel, which corresponds to the OAE1a, and the regionally distributed late Aptian Niveau Jacob have been studied with regard to changes in terrestrial vegetation patterns, terrigenous inputs and palaeofertility conditions. Palynological results from both black shale intervals exhibit a rich and stable floral pattern, dominated by various ferns, different types of cycads, bennettites as well as by several conifer families. Dinoflagellate cyst assemblages and the calcareous nannofossil-based nutrient index show no prominent changes in surface water productivity across the two studied intervals in the Vocontian basin. Significant variations are observed in terrestrial detrital input indicated by changes in absolute abundances of marine and terrestrial palynomorphs. According to our results, the laminated, OM-rich horizons of the Niveau Goguel interval reflect deposition during times of reduced siliciclastic input. Episodes of pronounced condensation were accompanied by anoxic conditions preventing degradation of the predominantly marine-derived OM. In contrast, the Niveau Jacob is characterised by a strong increase in terrestrial palynomorphs, most probably reflecting an abrupt increase in riverine runoff. The enhanced terrestrial OM input may have triggered oxygen-depletion in bottom waters, resulting in turn in increased OM preservation. Our results highlight the variety of processes that controlled the accumulation of OM in the Vocontian basin and they illustrate that enhanced surface water productivity is not an indispensable prerequisite for the formation of mid-Cretaceous black shales. © 2005 Elsevier B.V. All rights reserved.
Keywords: BLACK SHALE; CALCAREOUS NANNOFOSSILS; CRETACEOUS; DINOFLAGELLATE CYSTS; OAE; PALYNOMORPHS; Mesozoic::Cretaceous; Мезозой::Меловая